Condições de saúde e perda dentária na população do Brasil: pesquisa nacional de saúde (2013 e 2019) - Lima, Érica Nobre (2021)
INTRODUCTION: Diabetes mellitus (DM), hypertension (SAH), cardiovascular diseases (CVD), arthritis/rheumatism, depression and high cholesterol may be related to greater tooth loss, and there is no previous evidence from population- based studies in Brazil who investigated the effect of exposure to these diseases on tooth loss. OBJECTIVE: To assess the associations of health conditions with the loss of 13 or more teeth in Brazilian adults and elderly people in 2013 and 2019 and whether there is a change in the effect due to age in these relationships. METHODS: The National Health Survey (NHS) was a cross-sectional study with a sample of 60,202 participants in 2013 (>18 years) and 90,846 in 2019 (>15 years), living in private households in Brazil in urban and rural areas. The response variable was loss of 13 or more teeth. The explanatory variables are the presence of diabetes, hypertension, cardiovascular disease, arthritis/rheumatism, depression and high cholesterol. The magnitudes of the associations were measured using the prevalence ratio (PR) and their respective 95% CI, using Poisson Regression with sequential adjustment by: no adjustment (Model 1); macro-region and urban/rural region of Brazil (Model 2); sex, race/skin color and age (Model 3); current education (Model 4); smoking and alcohol abuse (Model 5). After complete adjustment, the interaction term between each exposure and age was included to verify the presence of modification and the effect of age on this relationship. Subsequently, the analysis was stratified by age group (≤34 years, 35 to 44 years, 45 to 54 years, 55 to 64 years and ≥65 years), following the same adjustments, except for age. Statistical analysis was performed using the Stata 15.0 statistical software, and to consider the complexity of the sample design, the weights were included using the svy command set of the statistical software. RESULTS: The prevalence of tooth loss in 2013 was 23.9% (95% CI: 23.2 – 24.6) in the total population and increased with age. In 2019, we observed a lower prevalence of tooth loss greater than 13 teeth for the total population (21.8%, 95% CI: 21.3 – 22.3), although a similar behavior was observed with advancing age. SAH, DM, depression, CVD, high cholesterol and arthritis/rheumatism are statistically associated with the loss of 13 or more teeth in the total population. Although chronic diseases are more often associated with tooth loss at older ages, our study found that only CVD were statistically associated with the loss of 13 or more teeth in the 65-year-old and older group in the 2019 analysis. presence of effect modification by age in this relationship, with higher prevalence ratios being identified in the 35 to 64 years old strata, and predominantly a decreasing trend with increasing age. CONCLUSION: SAH, DM, depression, CVD, high cholesterol and arthritis/rheumatism are associated with the loss of 13 or more teeth in the Brazilian population, and our results are relevant for directing public policies in the field of public health for prevention and treatment of these diseases. Among them, programs aimed at promoting oral health and controlling caries and periodontal disease, the main pathologies that increase the chances of early tooth loss in these individuals.